Effect of water stagnation on colonization of aonla (Emblica officinalis Gaertn.) by Arbuscular Mycorrhizae in Bundelkhand - Kumar, A.; Hashmi, S.; Shukla, A.; Jha, A. (Indian Journal of Agroforestry, 2020)
Water-stagnation of low lying areas is quite common in central India during rainy season, but little is known about its effect on colonization of trees by arbuscular mycorrhizal (AM) fungi. In this study, its effects on mycorrhization of aonla (Emblica officinalis Gaertn.) were evaluated. The results showed that mean colonization index was significantly higher in upland plants (22.7%) as compared to water logged plants (13.6%). Similar trend was recorded for AM spore count in upland (12 spores 100-1 soil) and lowland plants (7 spores 100-1 soil). In upland plants three AM species were recorded viz. Acaulospora scrobiculata Trappe, Glomus intraradix Schenck & Smith and an unidentified Glomus species. In lowland plants, only Glomus species (two) were prominent. Thus, the results suggested that Glomus species have better adaptability to water logged conditions and drainage in low lying areas should be proper for good mycorrhization of trees during rainy season.